Factors contributing to self-rated health in community-dwelling independent 75-year-old Finns: a population-based cross-sectional cohort study - Salminen, Marika; Luther-Tontasse, Emma; Koskenniemi, Jaana; Vahlberg, Tero; Wuorela, Maarit; Viitanen, Matti; Korhonen, Paeivi; Viikari, Laura (BMC, 2025)
Background Self-rated health (SRH) reflects biological, social, and functional aspects of an individual, incorporating personal and cultural beliefs as well as health behaviours. A deeper understanding of the structure of SRH can help health professionals focus on patients' personal health and functional goals and guide preventive health policies. This study aimed to examine the associations between SRH and independent factors by gender.
Methods The population-based, cross-sectional cohort study included 2,539 community-dwelling 75-year-old Finns who participated in the Turku Senior Health Clinic study. Data were collected through clinical examinations, questionnaires, and interviews, which included assessments of SRH, sociodemographic factors (living arrangements, education, self-rated financial status), psychosocial factors (sense of life meaningfulness, satisfaction with relationships, loneliness), health-related behaviours (smoking, alcohol use, physical activity), physical functioning (use of a mobility device, self-rated ability to walk 400 m, history of falls), and health conditions (pain, depressive symptoms, central obesity, vision, sleep quality, and number of self-reported diseases). A backward logistic regression analysis with an inclusion criterion of p < 0.001 was used to identify independent variables associated with SRH.
Results Fifty percent of both men and women reported having a poor SRH. There were no significant interactions between gender and independent variables regarding SRH. Independent variables associated with poor SRH were experiencing difficulties in walking 400 m (odds ratio 7.45, 95% confidence interval 4.91-11.30), being multimorbid (>= 6 diseases 6.00, 4.11-8.75; 2-5 diseases 2.97, 2.18-4.06), poor self-rated financial status (3.46, 2.82-4.24), lower levels of life meaningfulness (2.53, 2.07-3.11), having poor (2.34, 1.70-3.21) or moderate (1.58, 1.26-1.98) sleep quality, experiencing depressive symptoms (2.08, 1.57-2.77), reporting at least moderate (2.01, 1.59-2.54) or mild (1.31, 1.01-1.70) pain, and vision impairment (1.50, 1.21-1.86). The area under the curve of this model was 0.842.
Conclusions Our findings support early and proven prevention strategies for the most disabling chronic diseases, as well as promoting self-care management, physical activity, and muscle strength. Additionally, a balanced treatment approach that addresses vision impairments and manages symptoms such as pain, poor sleep, and depression is important for older adults' health.